Specific Involvement of Atypical PKCξ/PKMξ in Spinal Persistent Nociceptive Processing following Peripheral Inflammation in Rat. Issue 1 (5th November 2011) - Marchand, Fabien; D'Mello, Richard; Yip, Ping K; Calvo, Margarita; Muller, Emilie; Pezet, Sophie; Dickenson, Anthony H; McMahon, Stephen B
Background: Central sensitization requires the activation of various intracellular signalling pathways within spinal dorsal horn neurons, leading to a lowering of activation threshold and enhanced responsiveness of these cells. Such plasticity contributes to the manifestation of chronic pain states and displays a number of features of longterm potentiation (LTP), a ubiquitous neuronal mechanism of increased synaptic strength. Here we describe the role of a novel pathway involving atypical PKCξ/PKMξ in persistent spinal nociceptive processing, previously implicated in the maintenance of late-phase LTP. Results: Using both behavioral tests and in vivo electrophysiology in rats, we show that inhibition of this pathway, via spinal delivery of a myristoylated protein kinase C-ξ pseudo-substrate inhibitor, reduces both pain-related behaviors and the activity of deep dorsal horn wide dynamic range neurons (WDRs) following formalin administration. In addition, Complete Freund's Adjuvant (CFA)-induced mechanical and thermal hypersensitivity was also reduced by inhibition of PKCξ/PKMξ activity. Importantly, this inhibition did not affect acute pain or locomotor behavior in normal rats and interestingly, did not inhibited mechanical allodynia and hyperalgesia in neuropathic rats. Pain-related behaviors in both inflammatory models coincided with increased phosphorylation of PKCξ/PKMξ in dorsal horn neurons, specifically PKMξ phosphorylation in formalin rats. Finally, inhibition of PKCξ/PKMξ activity decreased the expression of Fos in response to formalin and CFA in both superficial and deep laminae of the dorsal horn. Conclusions: These results suggest that PKCξ, especially PKMξ isoform, is a significant factor involved in spinal persistent nociceptive processing, specifically, the manifestation of chronic pain states following peripheral inflammation.